Analysis of Teacher Consistency in Using Ice-Breaking Activities in Islamic Religious Education (PAI) at SMP Aisyiyah Terpadu Pagar Alam - Siti, Siti Nur Aisah; Disniarti, Disniarti (The Future of Education Journal, 2025)
This study aims to examine the consistency of teachers in using ice-breaking activities in the Islamic Religious Education (PAI) subject at SMP Aisyiyah Terpadu Pagar Alam. This research uses a qualitative method with a descriptive approach. The results show that teachers routinely use ice-breaking activities in their lessons. However, ice-breaking has not been included in the teaching module, so consistency has not been fully achieved. This is due to a discrepancy between what is implemented in the classroom and the documents being used. Factors supporting the consistency of teachers in using ice-breaking activities include school support and enthusiastic responses from students. Meanwhile, the inhibiting factors are the limited time teachers have to find ice-breaking ideas, the lack of training from the school, and some students struggling to understand the instructions during the ice-breaking session.